The Role of Training Program for Employees: Learning and Application (Journal of Governance and Development (JGD), 2015)
Training is considered as one of the significant progress in the human resource management function in the organization. Training and development programs for employees can act as a key driver of the implementation of strategic activities, which can be a support in the achievement of organizational goals. This program should be planned and implemented well, where it will increase the human resource planning and supporting the strategic direction of the organization. Based on this explanation, this paper attempts to describe the role of the implementation of training programs on employees in an organization, in order to improve their capability and managerial skills. This paper attempts to point out the importance of the relationship between input and output of training. The input of training intended is trainee characteristics, training design, and work environment, while the output of the training is learning and transfer of training. Transfer of training is the application of training materials in the workplace. This paper also attempts to identify the significant pathways of training input to the learning and application. The explanation for the first track is trainee characteristics, training design, and work environment on the learning and application, and then describes the path of trainee characteristics, training design, and work environment and learning as well on the application. The accomplishment of trainees transferring the knowledge and skill developed during training in their job is an important factor to measure the successfulness of training.